ANALISA WAKTU PENYELESAIAN PADA PROYEK PENINGKATAN JALAN KONSTRUKSI HRS BASE KELURAHAN BATUPLAT KOTA KUPANG DENGAN METODE EARNED VALUE - Yunior, Andriano Geovani Suban; Lulu, Laurensius; Usboko, Gregorius Paus (Eternitas: Jurnal Teknik Sipil, 2024)
A construction project is a series of activities to achieve a goal within certain time, cost and quality limits. Construction projects require resources, namely humans, materials, equipment, implementation methods, money, information and time (Kerzner 2009). Project resources are planned to achieve project goals within time, cost and quality constraints. The challenge in project implementation is how to plan an effective time schedule and efficient cost planning without reducing quality. In the road improvement project in Batuplat sub-district, the Earned Value method has not been applied as this method functions as a tool for evaluating project performance and the results of this evaluation can be used to estimate whether the project can be completed on time or not. From the results of initial observations, the author knows that in the project implementation process, weekly evaluations were not carried out, this could result in the contractor not knowing what obstacles could prevent the project from being completed on time. The author considers that the absence of this method cannot provide an estimate that this project can be completed on time because there are two possibilities that this project can be completed on time or not.